Numerical study on applicability of various swirl ratio definitions to characterization of tornado-like vortex flow field. Issue 220 (January 2022) - Wang, Mengen; Cao, Shuyang; Cao, Jinxin
Abstract: The swirl ratio is one of the key parameters for determining the tornado-like vortex structure. Various forms of definition of the swirl ratio have been employed in the physical and numerical modeling of tornado-like vortices, which makes the interpretation of a tornado-like vortex structure inconsistent. In this study, a series of large eddy simulations were performed to model stationary tornado-like vortices by considering two methods, with and without rotating downdraft at the inlet, to generate swirling flow. The evolution from single-vortex, to vortex-breakdown, to vortex-touchdown to multi-vortex flow configurations with increase in swirl ratio are presented, with analyses of various velocity and geometric ratios of simulated tornado-like vortices. Results show that the tornado-like vortex and its velocity and geometric ratios depend on whether or not there is a rotating downdraft when the swirl ratio is low, even when the dependence becomes weak at larger swirl ratios. A critical swirl ratio is discovered to be able to characterize the tornado's vortex structure, dimensionless velocity and geometric ratios. In addition, the various forms of definition of the swirl ratio correlate with each other in a linear or log-log-linear relationship, so they can be converted quantitatively to each other. Highlights: LES were performed to model tornado-like vortices with/without rotating downdraft. Effect of rotating downdraft on tornado-like flow field varies with swirl ratio. Different definitions of swirl ratio correlate with each other.